Kapton Based Antenna Simulation Analysis for Smart System - Dahalan, AH; Aziz, MZAA; Othman, M.A.; Nornikman, H; S. Ibrahim, (International Journal of Integrated Engineering, 2019)
This paper describes the analysis of Kapton material in antenna design for telecommunication systems. Kapton is usually used in the design of radio and microwave frequency antenna. It is a flexible material and with different dielectric value. The antenna is made of a Kapton substrate, a patch and copper (FR4). The dielectric characteristics of Kapton substrate changes according to temperature. The simulation result shows that the bandwidth of the antenna increased up to 10 MHz with a second layer of Kapton substrate. While the antenna gain decreased 1.19 dB when the dielectric value is increased. Computer Simulation Technology (CST) software was used to analyse the antennaâ€™s  performance.